Assessment of deforestation circumstances in Mokwa, Niger State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
This study investigated deforestation in Mokwa Local Government Area (MLGA) of Niger State. Simple and systematic random sampling technique was used in selecting the five communities and 120 respondents for the study, respectively. Questionnaire and informal interviews used includes discussion with the community heads, forest users, and personal observations from the field visited were the methods used to collect qualitative information. Findings revealed that the major occupations in the study areas are farming (60.0%), followed by artisan (22.5%) and civil servants (10.8%). As revealed by the respondents, the main circumstances of deforestation in the study areas includes the following: Fuel wood removal (37.5%), Timber logging (22.5%), and Farming (32.5%). It was discovered that global warming (32.5%) was the major consequence of circumstances of deforestation in the study areas, followed by soil erosion (29.2%), desertification (20.8%) and forests animal displacement (17.5%). It was revealed that some species of trees in the study areas have been going into extinction, such as Vitellaria paradoxa and Parkia biglobosa. This study concluded that the circumstances that have contributed to deforestation in MLGA are complex and multifaceted. Addressing this environmental issue requires a holistic approach that considers the interconnected factors driving deforestation and implements sustainable land management practices, conservation efforts, and community engagement initiatives. By understanding the circumstances leading to deforestation and taking proactive measures to address them, we can work towards preserving the natural resources and biodiversity of rural areas in Mokwa Local Government Area for future generations.
Keywords: Circumstances; Community; Deforestation; Forest